SEJARAH, PERAN DAN MODEL SKEMA PEMBIAYAAN TERINTEGRASI: ARTIKEL REVIEW TENTANG BEBERAPA STUDI KEUANGAN MIKRO SYARIAH - Nur Jamaludin (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2019)
This paper is to review the 5 selective aticles of Islamic Microfinance in order to highlight the crusial issues raised in the papers. The Findings of this article review is Islamic Micro Finance Institutions (IMFIs) is an effective tool to enhance the performance of Small Medium Entreprises and empower the poor society. Unfortunetelly, IMFIs have an ability to eradicate the poverty but still facing many problems to improve the capacity  the poorest of the poor people due to   financing in this group is very risk. Therefore, the social financing is needed to stimulate them, and one of the invention in microfinancing in this research is what we call as integrated financing schema for the poor which using waqaf instrument as a model of intervention to the poor society.